Essentials of Macroeconomics - Roger A. Arnold (Cengage Learning, Inc, 2005)
Shorter, more powerful, and easier to use. MACROECONOMICS, CONCISE EDITION covers all core economics topics including international trade and finance, helping you understand key topics in less time. Arnold also provides streamlined coverage of important macroeconomics concepts such as the relationship between money and banking, or fiscal policy. All this in just 24 chapters makes this the textbook that will help you succeed on the test and get ready for your first big job